Design and Evaluation for Target Indicated Torque Based Engine Starting Control Strategy in a High Pressure Common Rail Diesel Engine. (15th March 2016) - Lin, Xuedong; Han, Xiaomei; Li, Degang
Abstract : The diesel engine power demand of the start condition can be separated into two parts including resistance overcoming and acceleration realization for the reason that there is no power output during the starting process. The present paper mainly focuses on the fuel injection quantity control based on the engine power demand especially the acceleration demand for the resistance force is fixed for a specific engine, and the starting acceleration velocity is set as a target curve so that the acceleration process can also be fixed. The feasibility of the start control strategy proposed in this paper was verified by a comparison of the traditional starting control with a constant fuel quantity, and starting performance of the target acceleration based control shows predominance to the constant quantity control. And then the comparison between various starting acceleration processes, which was realized by the settings of acceleration curve slope factor, was conducted and results showed that the acceleration processes with higher slope factors perform better.